Herbicide and Application Timing Effects on Windmillgrass Control - Nicholas Mitchell; Jared Hoyle (Kansas Agricultural Experiment Station Research Reports, 2018)
Windmillgrass (Chloris verticillataNutt.) populations commonly infest turfgrass systems in the midwest, which result in aesthetically unacceptable turfgrass stands. Research trials were initiated in 2017 in Onaga and Junction City, KS, to determine windmillgrass control with various single herbicide applications at multiple application timings (spring, summer, and fall). Data collection for research trials consisted of visual percent windmillgrass cover (0–100%), line intersect analysis on four-inch spacing, normalized difference vegetation index (NDVI) (0 to 1 scale), and windmillgrass seedhead counts. Initial observations resulted in greater windmillgrass control with summer applications compared to fall applications. Pylex (topramezome) resulted in 80% windmillgrass control 8 weeks after summer application. Initial results indicate alternative herbicides options for windmillgrass control.
Keywords: windmillgrass; weed control; herbicide efficacy; herbicide timing